Geometry, 3D models and Virtual Reality to explain the mathematics of andalusian monumental heritage - Rodriguez, Jose L; Martinez-Sevilla, Alvaro; Alonso, Sergio (The electronic journal of mathematics & technology, 2024)
In this paper we address the construction of virtual reality scenarios for the NeoTrie VR software, to make some 3D models of architectural objects manageable anywhere. Students will be able to see the pieces (muqarnas, vaults and arches and towers) in a 3D model, manipulate and assemble them, to understand their spatial arrangement. They will also be able to use Neotrie tools to build and thus better assimilate the underlying geometric structures.